Micro RNA-Mediated Epigenetic Regulation in Hormonal Pathways: Insights into Thyroid Cancer Progression - Isha Rubab; Nafeesa Kainat; Alya Nazir; Zaineb Tariq; Sobia Sana; Yasmeen Sher; Kainat Abbasi; Ruqia Mehmood Baig (Indus Journal of Bioscience Research, 2025)
Thyroid cancer is the most prevalent endocrine malignancy, and its prevalence is continuously increasing globally. Thyroid cancer is a complicated disease that is impacted by environmental, genetic, and epigenetic factors. Among these, epigenetics, which are heritable variations in gene expression that do not include changes in the DNA sequence, has drawn much interest. The physiology and pathology of the thyroid gland depend heavily on hormonal pathways, especially those involving thyroid hormones. It has been demonstrated that their dysregulation promotes the development of tumors and the progression of cancer. MicroRNAs (miRNA or miRNAs) are key regulators of these epigenetic modifications. They modulate gene expression through chromatin remodeling, DNA methylation, and histone modifications, thereby influencing hormonal signaling pathways critical to thyroid physiology and pathology. Dysregulation of miRNA can disrupt thyroid hormone signaling, affect the expression of hormone-responsive genes and receptors, and contribute to tumor initiation, progression, and metastasis. Recent studies highlight the interplay between thyroid hormone signaling and miRNA-mediated epigenetic regulation in thyroid cancer. Understanding these molecular mechanisms is crucial for the development of novel diagnostic biomarkers and targeted therapeutic strategies.